Penegakan Hukum Terhadap Pelaku Penyerobotan Tanah Di Wilayah Gunung Sitoli Sumatera Utara - Sukur Yanus Zai (Direktorat Penelitian dan Pengabdian (DPPM) Universitas Pelita Bangsa, 2025)
Land grabbing is an unlawful act that harms legitimate landowners and creates legal uncertainty within society. This study examines law enforcement in cases of land grabbing in Gunung Sitoli, North Sumatra, which faces various structural and cultural challenges. One of the main obstacles is the weak formal ownership documentation, as many local residents do not possess land certificates despite having occupied the land for generations. Additionally, the limited capacity of agrarian investigators, restricted access to land information, and conflicts between customary law and positive law further complicate the issue. The presence of land mafia practices, collusion with officials, and weak criminal sanctions worsen the situation. Although restorative justice has been applied in minor cases, this approach is considered inadequate for serious offenses involving intimidation and violence. To effectively enforce the law, there needs to be better teamwork between different agencies, training for investigators, faster progress on the Systematic Land Registration Program (PTSL), and changes in regulations that officially acknowledge the rights of indigenous communities